Effects of Food Fit for Fun Program with Social Media Used on Health Literacy and Obesity Prevention Behaviors among Senior-Primary School Students, in Nakhon Ratchasima Province Thailand (Indian Journal of Public Health Research & Development, 2020)
Background: Childhood obesity has become more prevalent all over the globe. In Thailand, the highestprevalence rate of childhood obesity has been found among primary school students in Northeastern (9.9%),which still exceeds 7% recommended by the WHO.Objective: This study aimed to assess the effectiveness of Food Fit for Fun program with social mediaused on health literacy and obesity prevention behaviors among senior-primary school students in NakhonRatchasima Province, Thailand.Methods: A quasi-experimental was conducted. An experimental and a control group each with 34participants. A 12-week program was implemented with Health Literacy on dietary and physical activitiesand social media were used for communication and support. Analysis of the data was performed using t-testwhile a mean difference and 95%CI were used for determining statistical significance.Results: The senior-primary school children in the experimental group improved their mean differenceon health literacy in preventing obesity (10.18; 95% CI: 7.11 to 13.24, p-value
Keywords: Childhood Obesity, Health Literacy, Behavioral Modification.